Examining user acceptance and adoption of the internet of things - Yang Lu (International Journal of Business Science & Applied Management (IJBSAM), 2021)
The Internet of Things (IoT) promises a new technological paradigm that can offer a number of innovative applications and services targeting different scopes of adoption. The full potential impact of the IoT is enormous due to its pervasive nature and the rapid improvement of enabling technologies. Taking lessons from information technology and systems in their early stages, a low degree of user acceptance would hinder the progress of IoT implementation. Studies of the IoT from the user perspective mainly investigated factors influencing acceptance and use of a specific service or application. A comprehensive view of users' attitude toward the IoT platform may offer further insights. Drawing upon the Diffusion of Innovation Theory and the Technology Acceptance Model, this study examined six potential determinants of users' adoption of the IoT platform and tested two potential psychological outcomes. Using data collected from 615 potential users and analysing with structural equation modelling techniques, the results and findings of this study contribute to facilitating understandings of IoT acceptance and adoption.
Keywords: 650; Internet of Things; Technology acceptance; Diffusion of Innovation; Structural equation modelling